Analisis Kesalahan Berbahasa pada Media Daring di Dompu - Lili Suryaningsih; Sukarddin Sukarddin; Sugerman Sugerman; Eka Yulianti; Fitriani Fitriani (Departement of Mathematics Education, 2024)
Analysis of language errors on online media in Dompu is an activity to identify errors in the use of languge that deviates from the norms of Indonesian grammar rules in newspapers through online media. Based on the many errors in writing online newspapers in Dompu, the researchers are interested in conducting research on the form of language errors in online media in Dompu. The purpose of this study is to describe the form of language errors in online media using a qualitative descriptive method. The data of this research are language errors in newspapers in Dompu in the form of text with data collection techniques used in solving this research problem and using documentation techniques, reading techniques, and note-taking techniques. Then the data source in this study uses secondary data sources. The results of this study indicate language errors in online newspapers in Dompu include morphological aspects, namely affixation and reduplication, while from the syntactic aspect, namely effective sentences and senteces structure. However, there were still some errors found including errors in affixation, use of hyphens, use of prepositions and conjunctions, effective sentences and sentence structure. Language errors in online newspapers are the use of language, both oral and written, which deviates from the norms of Indonesian grammar rules that do not use guidelines or references in communicating